2012
DOI: 10.1088/1741-2560/9/2/026007
|View full text |Cite
|
Sign up to set email alerts
|

Error-related electrocorticographic activity in humans during continuous movements

Abstract: Brain-machine interface (BMI) devices make errors in decoding. Detecting these errors online from neuronal activity can improve BMI performance by modifying the decoding algorithm and by correcting the errors made. Here, we study the neuronal correlates of two different types of errors which can both be employed in BMI: (i) the execution error, due to inaccurate decoding of the subjects' movement intention; (ii) the outcome error, due to not achieving the goal of the movement. We demonstrate that, in electroco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
64
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(76 citation statements)
references
References 62 publications
(70 reference statements)
9
64
0
1
Order By: Relevance
“…Importantly, error-related signals are not only present in EEG, but several works have shown their existence also in semiinvasive [19] and invasive recording methods [20]. As future work, it is still pending to test the proposed results with a larger pool of subjects, and the feasibility of decoding this signal with closed-loop experiments.…”
Section: Discussionmentioning
confidence: 95%
“…Importantly, error-related signals are not only present in EEG, but several works have shown their existence also in semiinvasive [19] and invasive recording methods [20]. As future work, it is still pending to test the proposed results with a larger pool of subjects, and the feasibility of decoding this signal with closed-loop experiments.…”
Section: Discussionmentioning
confidence: 95%
“…A statistical significance test based on bootstrapping was run over the ERSs following the method described in [20]. O2 P8 P4 CP6 T8 C4 FC6 F8 F4 AF4 Fp2 Oz Pz CP2 CPz CP1 Cz FC2 FCz FC1 Fz O1 P7 P3 CP5 T7 C3 FC5 F7 F3 AF3 P8 P4 CP6 T8 C4 FC6 F8 F4 AF4 Fp2 Oz Pz CP2 CPz CP1 Cz FC2 FCz FC1 Fz O1 P7 P3 CP5 T7 C3 FC5 F7 F3 AF3 Fp1 alpha band (8)(9)(10)(11)(12) Fz O1 P7 P3 CP5 T7 C3 FC5 F7 F3 AF3 O2 P8 P4 CP6 T8 C4 FC6 F8 F4 AF4 Fp2 Oz Pz CP2 CPz CP1 Cz FC2 FCz FC1 Fz O1 P7 P3 CP5 T7 C3 FC5 F7 F3 AF3 P8 P4 CP6 T8 C4 FC6 F8 F4 AF4 Fp2 Oz Pz CP2 CPz CP1 Cz FC2 FCz FC1 Fz O1 P7 P3 CP5 T7 C3 FC5 F7 F3 AF3 Fp1 P8 P4 CP6 T8 C4 FC6 F8 F4 AF4 Fp2 Oz Pz CP2 CPz CP1 Cz FC2 FCz FC1 Fz O1 P7 P3 CP5 T7 C3 FC5 F7 F3 AF3 Fp1 CENTRAL REGION LEFT HEMISPHERE RIGHT HEMISPHERE CENTRAL REGION LEFT HEMISPHERE RIGHT HEMISPHERE CENTRAL REGION LEFT HEMISPHERE RIGHT HEMISPHERE Fig. 2.…”
Section: Analysis Of Continuous Error Evaluationmentioning
confidence: 99%
“…Furthermore, they rely on discrete tasks, where the signals were detected in a synchronous fashion. A recent work has shown that it is possible to asynchronously detect errors during tasks where a device performs continuous trajectories using ECoG [10]. In this asynchronous setting, there are no explicit correct events since the device is continuously moving.…”
mentioning
confidence: 99%
“…1,2,6-8, 10,11,[19][20][21][22][23][24][25][26][27][28][29]35 On the other hand, there is a relative dearth of SEEG-related BMI studies. 18,30 Previous SEEG BMI studies have demonstrated the possibility of using SEEG electrodes in communication BMIs in which letters were selected by involuntary brain responses.…”
Section: Discussionmentioning
confidence: 99%
“…32 Whereas SEEG was originally described by Bancaud et al in 1965, 3 it has only become increasingly used in the US since 2009. 14,32 Brain-machine interfacing is an area of research that is increasingly taking place in tandem with invasive brain monitoring for epilepsy, 1,2,[6][7][8]10,11,[18][19][20][21][22][23][24][25][26][27][28][29][30]35 even though BMI systems are being developed primarily for paralyzed individuals. Brain-machine interface systems "decode" some aspect of brain processing in real time and use that decoded information to control an assistive device.…”
mentioning
confidence: 99%